Optimizing Lawrence Meir Friedman's Legal System Theory in the Authority to Investigate Corruption Crimes in Indonesia - Fahrizal S.Siagian (JUSTICES: Journal of Law, 2023)
This study aims to answer the regulation of eradicating corruption in Indonesia, second, answer the optimization of Lawrence Meir Friedman's legal system in the authority to investigate corruption crimes in Indonesia. The research method used is normative legal research which refers to research studies on laws and regulations combined with primary, secondary and tertiary legal materials. The data collection technique is by using (Library Research). The nature of research is descriptive analysis. First The results of the study, the Eradication of Corruption Crime is regulated in Law Number 20 of 2001 and other laws and regulations. Second, that the investigation of corruption crimes in Indonesia has not been perfect in accordance with the theory of Lawrence Meir Friedman's legal system. The problems of the three elements of the legal system are still an obstacle to investigating corruption crimes in Indonesia.